(7-3x)(4-1x)=

Simple and best practice solution for (7-3x)(4-1x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7-3x)(4-1x)= equation:


Simplifying
(7 + -3x)(4 + -1x) = 0

Multiply (7 + -3x) * (4 + -1x)
(7(4 + -1x) + -3x * (4 + -1x)) = 0
((4 * 7 + -1x * 7) + -3x * (4 + -1x)) = 0
((28 + -7x) + -3x * (4 + -1x)) = 0
(28 + -7x + (4 * -3x + -1x * -3x)) = 0
(28 + -7x + (-12x + 3x2)) = 0

Combine like terms: -7x + -12x = -19x
(28 + -19x + 3x2) = 0

Solving
28 + -19x + 3x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(7 + -3x)(4 + -1x) = 0

Subproblem 1

Set the factor '(7 + -3x)' equal to zero and attempt to solve: Simplifying 7 + -3x = 0 Solving 7 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = 0 + -7 -3x = 0 + -7 Combine like terms: 0 + -7 = -7 -3x = -7 Divide each side by '-3'. x = 2.333333333 Simplifying x = 2.333333333

Subproblem 2

Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4

Solution

x = {2.333333333, 4}

See similar equations:

| 13x-21=46 | | x-7=24 | | 8x^3+40x^2-288x= | | 5(x+2)-2x(3x-1)=13 | | 0=x^2+5x-15 | | 2x+5=x+13 | | 300-90= | | 25*12= | | 4x^2-16x+24=0 | | 2(4a+3)=16 | | x-4y=-13 | | 6x+19=1056 | | -2(x-3)=10 | | x-9=3x+11 | | 6x-8=8x+2 | | C^2-4c=-3 | | -q^2+5q-4=0 | | r^2+4r+6=0 | | x+78+x+a+87=199 | | b^2-5b-6=0 | | K^2-7k+12=0 | | 3y-2x=15 | | 48+7m=174 | | 25x-96=104 | | 2x^2-20x+82=0 | | 7+3(x+2)=4(x-1) | | 2x-(3-(4-3x))+6= | | (W+6)(w-15)=0 | | (2c-4)= | | x+23-45=4x+34 | | 93567489e= | | 1e= |

Equations solver categories